Fatores de risco para lesão renal e avaliação das características clínicas e laboratoriais na disfunção do trato urinário inferior em criançase adolescentes - Cristiane Reis Leonardo (2006)
Introduction - The aim of this study was to evaluate the clinical end laboratorial parameters and risk factors for renal scarring in lower urinary tract dysfunction (LUTD) in children and adolescents who were referred to the LUTD out patients department (OPD) at the Hospital das Clínicas - UFMG, from 1996 to 2004. This study was composed of 2 periods of time: T0 and T1. During T0, the patients (pcts) were analyzed after their initial screening and before treatment by the OPD team. The T1 analyzed thepcts after treatment and follow up by the out patients department team.Methods - The T0 consisted of 2 parts. The first one analyzed 120 children, aged 7,3 + 4,5 years, in order to search risk factors for renal scarring formation. The second part divided these children into 2 groups according to the cause of LUTD: NG neurogenic group - 82 pcts and NNG - non-neurogenic group - 38 pcts. These groups were studiedconcerning their clinical, sonographic and urodynamic parameters as their previous treatment. At the T1, 113 of 120 first pcts were also divided into NG (78 pcts, aged 10 + 5,3) and NNG (35 pcts, aged. 11,9 anos + 3,7) and their parameters (clinical, sonographic and urodynamic ), after the follow up period, were compared to their own parameters at the T0, before treatment. At the T1, the management by the OPD wasevaluated. In order to define risk factors for renal scarring pcts were evaluated concerning gender, kind of LUTD (neurogenic or idiopathic), vesicoureteral reflux (VUR), low bladder capacity and increased bladder capacity (according to age and ICCS recommendation), uninhibited bladder contractions (UBC), residual urine (>20% bladder capacity), symptomatic urinary tract infection (UTI) and asymptomaticbacteriúria, constipation, detrusor-esphincter dissinergia, increased detrusor pressure (>40cm water), low compliance and thickness of the bladder wall. Renal scarring were diagnosed by DMSA (105 pcts), excretory urography (2 pcts) and by at least 2 consecutive ultrasound scans showing no scarring (13 pcts). Association betweenindependent variables and renal scarring and between groups were assessed by Chi square or Fisher exact test and by the Students t test or Mann-Whitney test for univariate analysis. Logistic regression was used for multivariate analysis of the risc factors for renal scarring. The Mc Nemar and t-paired tests determined the comparison between the same pacts in T0 and T1. P< 0,05, 95% confidence interval was consideredsignificant. Results - Renal scarring was noted in 38 pcts (31%), 31,7% of the NG and 31,5% of the NNG. The risk factors for renal scarring were VUR (p<0001) and female gender (p=0,05). Thickness of the bladder wall was a marginal risk factor (p = 0,07). Although UTI was not a risk factor for renal scarring, there was association between this parameter and VUR (p=0,03). Urinary incontinence was present in 88% of the NG and73,6% of the NNG; constipation in 39,4% of the NG and 18,9% of the NNG; UTI in 51% of the NG and 52% of the NNG; asymptomatic bacteriuria in 52,4% of the NG and 31,5% of the NNG; VUR in 23,7% of the NG and 36,3% of the NNG; renal scarring in 31,7% of the NG and 31,5% of the NNG; hypertension in 4,9% of the NG (0 of the NNG); UBC in 65,5% of the NG and 69,2 of the NNG; low compliance in 82,8 of theNG and 52,2% of the NNG; detrusor-sphincter dissinergia in 75,5% of the NG and 47,3% of the NNG; low bladder capacity in 57,3% of the NG and 26,3% of the NNG; residual urine in 78,2% of the NG and 38,2% of the NNG; thick walled bladder in 42,1% of the NG and 20,5% of the NNG; trabeculation in 39,4 of the NG and 8,8% of the NNG. During the T1, there was increasing use of anticholinergic medication and clean intermittent catheterization (CIC) in the NG. The use of prophylactic antibiotic decreased in both groups. Although it had been prescribed by the OPD doctors, the use of medication for constipation didnt increase in the follow up period in both groups. At the end of T1, urinary incontinence was still present in 68% of the NG. Constipation and asymptomatic bacteriúria had increased in both groups. Asymptomatic bacteriuria was associated to CIC (p = 0,004) and constipation (p = 0,04) and it was not associatedto scar formation (p=1). Although it disappeared in 14% of the NNG, there was no improvement of the VUR in the NG. Nine pcts formed new scarring 5 in scarred kidneys and 4 in normal kidneys (1 in the NG and 3 in the NNG), during the follow up. Two new pcts presented with hypertension (NG) and it was associated with renal scarring (p=0,005). There was no significant improvement of the thickness of the bladder wall in the NG, as the low compliance, low bladder capacity or dissinergia inthe NG. In the NGG there was improvement of the bladder wall, with 12% of the pcts presenting with thickness of the bladder wall at the end of the follow up. Residual urine didnt improve during the follow up in both groups, however it was well managed by using CIC or timely micturation or micturation at 2 times. Conclusion - VUR was the main risk factor for renal scarring followed by the female gender. Thickness of the bladder wall was a marginal risk factor. Although UTI was not a risk factor for renal scarring, there was association between this parameter and VURin order to formation of renal scarring. There was no association between VUR and bladder pressure. Asymptomatic bacteriuria shouldnt be treated. Despite the increasing in asymptomatic bacteriuria and decreasing in prophylaxis, there was no increasing in UTI nor association between scarring and asymptomatic bacteriuria. There was noimprovement of the thickness of the bladder wall in the NG, as the parameters related to the bladder wall in this group. Concerning urinary incontinence, although it had improved over the follow up, its results arent still satisfactory. The low incidence of scarring during the follow up showed that the treatment proposed by the LUTD OPD was adequate. In order to improve renal outcome in the LUTD, diagnose and management of these pcts must be precocious. An education program should bevaluable to advise primary care doctors about the morbidity of LUTD in children and adolescents.